2010
DOI: 10.1126/science.1183068
|View full text |Cite
|
Sign up to set email alerts
|

Punishers Benefit From Third-Party Punishment in Fish

Abstract: H uman studies show that uninvolved bystanders often pay to punish defectors (1, 2). Such behavior has typically been interpreted in terms of group-level benefits (3) despite theoretical predictions that third-party punishment can yield individual benefits to the punisher (4). Here, we show that male cleaner fish, Labroides dimidiatus, punish their female partners if females cheat while inspecting model clients. Punishment promotes female cooperation, yielding direct foraging benefits to the male. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
120
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 7 publications
5
120
1
Order By: Relevance
“…Policing in social insects is a special case since the destruction of eggs for the benefit of the remainder of the hive benefits the punishers indirectly through kin benefits (Ratnieks & Wenseleers 2008), a point that will be expanded upon in §4. In one experiment, male cleaner fish aggressed against female partners for 'cheating' by taking the preferred food from a plastic plate, resulting in the immediate removal of the common food source (Raihani et al 2010). As a result, the females were less likely to take the preferred food in subsequent trials.…”
Section: Gros-louis 2004)mentioning
confidence: 99%
See 1 more Smart Citation
“…Policing in social insects is a special case since the destruction of eggs for the benefit of the remainder of the hive benefits the punishers indirectly through kin benefits (Ratnieks & Wenseleers 2008), a point that will be expanded upon in §4. In one experiment, male cleaner fish aggressed against female partners for 'cheating' by taking the preferred food from a plastic plate, resulting in the immediate removal of the common food source (Raihani et al 2010). As a result, the females were less likely to take the preferred food in subsequent trials.…”
Section: Gros-louis 2004)mentioning
confidence: 99%
“…As a result, the females were less likely to take the preferred food in subsequent trials. While Raihani et al's (2010) study was designed to make a point about third-party functional punishment, it was actually a test of second-party functional punishment since there was no third party, and since the punisher benefited directly by altering the behaviour of his partner to his benefit. While clients may benefit in natural settings, this study demonstrated that third-party benefits would be a by-product of a coercive strategy.…”
Section: Gros-louis 2004)mentioning
confidence: 99%
“…Punishment can increase cooperation levels if there are opportunities to punish defectors, that is, decreasing a defector's immediate payoff at a personal immediate cost (Fehr & Gächter, 2002;Raihani et al, 2010;Raihani et al, 2012;Sigmund, 2007). Until recently, such costly punishment has been perceived as an evolutionary puzzle because punishers accept costs to harm others while third parties benefit from the increased cooperation levels (Dreber et al, 2008;Fehr & Gächter, 2002;Rankin et al, 2009;Sigmund, 2007;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, punishment is rarely observed outside the context of human society 27 , mainly because most intraspecific aggression results in an immediate benefit for the aggressor, thereby qualifying as a form of direct competition 19,26 . A few studies have explicitly demonstrated the punishment of non-cooperative behaviour in birds 2 and fish 28 , but its scarcity in primates is surprising given the importance of punishment in human societies 25,27 . Further, punishment seldom leads to clear behavioural modifications (that is, increased cooperation or decreased competition) in the punished parties 29 , and there is some debate about the importance of behavioural modification in the evolution of punishment 30 .…”
mentioning
confidence: 99%